ANALISIS PARAMETER KUALITAS AIR SUNGAI KAMPUNG SALAK KOTA SORONG PAPUA BARAT DAYA: Analisis Parameter Kualitas air Sungai kampung Salak - Ayu, Desilvi; Mirino, Tracey; Alfius, Benyamin (Casuarina: Jurnal Teknik Lingkungan, 2024)
The Kampung Salak River in the city of Sorong, Southwest Papua, is a vital source of water for the local community. However, the water quality of the river has become a concern due to various environmental and anthropogenic factors. This study aims to analyze the physical and chemical parameters. The research methodology involves collecting water samples with three replications taken in the morning, afternoon, and evening. The samples are analyzed at the Environmental Engineering Laboratory of Muhammadiyah University Faculty using quantitative methods. The research results show that physical parameters such as temperature,  conductivity, and TDS are within acceptable limits, and chemical parameters such as pH range from 6.5 to 6.9.  The TDS values range from 180 to 255 mg/L, the SALT values range from 133 to 178 psu, the temperature is 30°C, and the conductivity values range from 2.75 to 38.1 µmho/cm.